Communication of Aggregate Preferences Through Market Prices - Kraus, Alan; Sick, Gordon A. (Journal of Financial and Quantitative Analysis, 1979)
Alan Kraus, Gordon A. Sick, Communication of Aggregate Preferences Through Market Prices, The Journal of Financial and Quantitative Analysis, Vol. 14, No. 4, Proceedings of 14th Annual Conference of the Western Finance Association, June 21-23, 1979 (Nov., 1979), pp. 695-703